A RARE CASE OF CONTRALATERAL RECURRENCE OF AN ALDOSTERONE-PRODUCING ADENOMA - S, Tivya; HR, Ijaz; AR, Anilah (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Primary aldosteronism is commonly caused by unilateral aldosterone producing adenoma (APA) or bilateral idiopathic hyperaldosteronism. Laparoscopic adrenalectomy for unilateral disease is usually curable and is the treatment of choice. Recurrent APA after an adrenalectomy on the same side is extremely rare. Contralateral recurrence of an aldosterone producing adenoma (APA) in a previously normal adrenal gland after the initial adrenalectomy is also exceedingly rare. CASE We report a 31-year-old Malay male who first presented in 2009 with hypertension, hypokalemia and metabolic alkalosis. Investigation for hypertension in the young revealed primary aldosteronism (elevated aldosterone renin ratio, ARR and a nonsuppressible aldosterone on confirmatory testing). CT scan of the adrenal glands revealed a right adrenal adenoma measuring 1.9 cm x 0.9 cm with a normal left adrenal. He was diagnosed with Conn’s syndrome and underwent laparoscopic right adrenalectomy. HPE of the right adrenal was consistent with adrenocortical adenoma. Post operatively, hypokalemia resolved and he was discharged with only a single antihypertensive agent. He subsequently defaulted his medication and was lost to follow up. He presented 8 years later in 2017 with hypertensive intracranial bleed. He was again found to have hypokalemia with metabolic alkalosis and investigations revealed recurrent primary aldosteronism. CT adrenals showed left adrenal adenoma measuring 1.3 cm x 1.2 cm. A lesion was also seen at the previous right adrenalectomy site adjacent to the surgical clips. Possibility of recurrent disease on the right side or contralateral left APA was entertained. We proceeded with adrenal vein sampling (AVS) which confirmed a left APA. CONCLUSION He was started on spironolactone and his BP is currently well controlled with normal potassium levels.